Community enthusiasm in developing Ombilin coal-mining industrial heritage in Sawahlunto, West Sumatera - Reagan Brian; Dina Mayasari Soeswoyo; Jeffry Sudirja; Willy Arafah; Rahmat Ingkadijaya; Himawan Brahmantyo; Sundring Pantja Djati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The purpose of this research is to gain an understanding of the community's attitudes toward the development of Sawahlunto, West Sumatera, Indonesia as an industrial heritage tourism destination. This research used mix method – explanatory sequential design with a case study approach, to explore real conditions in life as well as a contemporary setting or context. Community attitudes were measured using questionnaires and deepened by interviews, observations, and focus group discussions. The finding of this study shows the enthusiasm of the local community in developing Obillin tourism in order to preserve as well as revitalize it so that it can benefit the community. The results of this study can be important for policymakers regarding sustainable tourism development.